Kinematic and kinetic comparison between preprofessional pitchers from the Dominican Republic and the United States - Nicholson, Kristen F.; Mylott, Joseph A.; Hulburt, Tessa C.; Hamer, Tyler J.; Bullock, Garrett S. (Frontiers in Sports and Active Living, 2023)
Introduction: The purpose of this study was to compare elbow varus torque and shoulder distraction force in pre-professional United States (US) and Dominican Republic (DR) pitchers. Kinematics that are known to influence elbow varus torque and shoulder distraction force were also compared. Methods: A retrospective review was performed on baseball pitchers from the DR and US who participated in biomechanical evaluations conducted by the University biomechanics laboratory personnel. Three dimensional biomechanical analyses were performed on US (n = 37) and DR (n = 37) baseball pitchers. Potential differences between US and DR pitchers were assessed through analysis of covariance with 95% confidence intervals (95% CI). Results: Pre-professional DR pitchers were found to throw fastballs with slower hand velocity (DR: 3,967.1 (939.4); US: 5,109.1 (613.8); Beta: 1129.5 (95% CI: 677.5, 1581.4) °/s), but experienced increased elbow varus torque compared to their US counterparts (DR: 7.5 (1.1); US: 5.9 (1.1); Beta: -2.0 (95% CI: -2.7, -1.2) %BWxH). DR and US pitchers demonstrated similar shoulder distraction force (DR: 136.8 (23.8); US: 155.0 (25.7); Beta: 0.4 (95% CI: -1.2, 19.7) %BW). Discussion: Increased elbow varus torque despite decreased pitch velocity suggest inefficient pitching mechanics among DR pitchers. Inefficient pitching mechanics and increased elbow torque should be considered when developing training programs and pitching plans for professional pitchers from the Dominican Republic.